Penerapan Kegiatan Kolase Setelah Menjiplak di Atas Sketsa Bergambar untuk Meningkatkan Aspek Perkembangan Motorik Halus Anak Usia 4-5 Tahun Di TK Aisyiyah Bustanul Athfal II Perumnas - Ahmad Afiif; Bunga; Besse Marjani Alwi; Nurkhalisah Latuconsinah; Hasnawati Sade (Faculty of Tarbiyah and Teacher Training, 2023)
The importance of increasing fine motor development in early childhood so that children carry out motor movements and activate their eyes with interesting and unique activities. Fine motor development in children, especially tracing by pasting grains on the child's tracing results. This study aims to determine the extent to which aspects of children's motor development are improved by tracing activities and then the results of the child's tracings are attached with green beans and peanuts at the age of 4-5 years. This community service research in the form of service learning was conducted at Aisyiyah Bustanul Athfal II Kindergarten with a total of 5 children. The instruments used are animal sketches, observation sheets for children and evaluation of the implementation of the intervention. Data were analyzed using descriptive statistics. The results showed that children were able to trace through pictorial sketches, then green seeds and peanuts were attached to the tracing results. The findings in this study imply that by applying the collage activity after tracing, it can train children's fingers to choose the seeds to be pasted on top of the tracing.